Pengaruh Beban Kerja, Kepuasan Kerja, Dan Work Life Balance Terhadap Kinerja Karyawan Pt. Multimestika Daya Semesta - Malvin Teddy; Elva Angelia Astakho; Fajar Rezeki Ananda Lubis; Thezar Fiqih Hidayat Hasibuan (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this study was conducted in order to see the strong influence of workload, job satisfaction, and work life balance to employee performance. A hundred respondents were sampled and used simple random sampling techniques, as well as multiple linear analysis. Data was taken from interviews and filling out questionnaires. The calculation of H1 (Workload variable) is tcount (3.697) > ttable (1.985) and sig (0.000) < (0.05), has a positive and significant influence. The calculation of H2 (Job satisfaction variable) is tcount (3.704) > ttable (1.985) and sig (0.000) < (0.05), has a positive and significant effect. Calculation of H3 (Worklife balance variable) is tcount (3.697) > ttable (1.985) and sig (0.000) < (0.05), has a positive and significant effect. calculation of H4 (Workload variable, job satisfaction, work life balance) is Fhitung (210.395) > Ftabel (3.09) and sig (0.000) < (0.05), together have a positive and significant effect. Keywords: Workload, Job Satisfaction, Work Life Balance, Employee Performance